TOKO KOPI DAN KAFE DI BANJARBARU - Salsabila, Riestya Zalfa Elfrinanda; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
In the city of Banjarbaru, the growth of the coffee shop industry is now accelerating. This is evident from the large number of coffee shops that have appeared since it has become a way of life for the majority of individuals in modern society. The design of the Coffee Shop in Banjarbaru must prioritize visitor comfort and satisfaction. This requires a calm atmosphere in the midst of busy activities in the cafe. To realize this need, it is necessary to have good spatial organization by taking into account the environment around the design area and user needs. With a flexible space intended to accommodate students and the general public to work, communicate, cooperate, discuss, and other activities that can improve each individual's ideas, this design solution is created based on the Collaborative Coffee Shop concept.